Characterization of a Salmonella typhimurium aro vaccine strain expressing the P.69 antigen of Bordetella pertussis. - Strugnell, R (1992)
The P.69 Bordetella pertussis protective antigen was expressed by use of the trc promoter from the chromosome of a Salmonella typhimurium aro vaccine strain, BRD509, by integrating the prn gene, encoding the 93-kDa precursor of this protein, into the aroC locus. P.69 was detected on the cell surface of the S. typhimurium strain (BRD640) by agglutination and immunoelectron microscopy. BALB/c mice immunized orally or intravenously with BRD640 showed a significant level of protection against an aerosol challenge with virulent B. pertussis, compared with control animals. No anti-P.69 antibodies in the serum or anti-P.69 antibody-secreting cells in the lungs were detected in BRD640-vaccinated animals, although cells isolated from spleens showed a P.69-dependent cell proliferative response. In contrast, low levels of anti-P.69 antibodies in the serum and anti-P.69 antibody-secreting cells in the lungs were detected in immunized mice following a B. pertussis challenge.